Fabrication of latex rubber reinforced with micellar nanoparticle as an interface modifier. (June 2016) - Kim, Sanghoon; Adkins, Jason; Biswas, Atanu
Reinforced latex rubbers were fabricated by incorporating small amount of nanoparticles as interface modifier. The rubbers were fabricated in a compression mold at 130 ° C. The incorporated nanoparticles were prepared from wheat protein (gliadin) and ethyl cyanoacrylate (ECA). These nanoparticles were disintegrated to the constituent amphiphilic block copolymers while mixing with latex suspension and adsorbed on the surface of latex particles. The disintegration of nanoparticles and adsorption of the constituent amphiphilic block copolymers on the surface of latex particles were investigated by dynamic light scattering. The improved mechanical properties of the produced reinforced latex rubbers were characterized by mechanical analysis (stress–strain) and hardness test. Incorporation of nanoparticle into latex improved most of the mechanical properties, such as tensile strength, % elongation, energy at break, and toughness by 30% to 300%. On the other hand, tensile modulus and hardness were not much affected by the incorporation of nanoparticles. This research showed that the optimum percentage of nanoparticle is 2%, and the optimum gliadin:ECA weight ratio is 3:1.